Pengaruh Bandwagon Effect, Content Marketing, dan Viral Marketing terhadap Keputusan Pembelian Skincare MS Glow dengan Perilaku Konsumtif Sebagai Variabel Mediasi - Elsa Ramada Putri; Rino Rino (Jurnal Ecogen, 2025)
This study aims to analyze the influence of the bandwagon effect, content marketing, and viral marketing on MS Glow skincare purchasing decisions with consumer behavior as a mediating variable for students at Padang State University. This type of research is causative research. The population in this study were students at Padang State University who had purchased MS Glow skincare products. The determination of the number of samples using the formula of Hair et al. is 270 samples. This study uses a nonprobability sampling technique. The data used are primary data with predetermined criteria. The analysis method used is SEM using SmartPLS 4.0. The results of the study show that (1) Bandwagon effect has a positive and significant effect on purchasing decisions. (2) Content marketing has a positive and significant effect on purchasing decisions. (3) Viral marketing has a positive and significant effect on purchasing decisions. (4) Bandwagon effect has a positive and significant effect on consumer behavior. (5) Content marketing has a positive and significant effect on consumer behavior. (6) Viral marketing has a positive and significant effect on consumer behavior. (7) Consumer behavior has a positive and significant effect on purchasing decisions. (8) Bandwagon effect has a positive and significant effect on purchasing decisions with consumer behavior as a mediating variable. (9) Content marketing has a positive and significant effect on purchasing decisions with consumer behavior as a mediating variable. (10) Viral marketing has a positive and significant effect on purchasing decisions with consumer behavior as a mediating variable.